Changes in the Attitude and Practice Toward End-of-Life Care: Perspective of Chinese Physicians in Medical Department. (August 2015) - Lam, K. W.; Yeung, K. W. Au; Lai, K. Y.; Cheng, F.
Introduction: End-of-life care is affected by the attitude and cultural influence of doctors. Methods: To investigate the attitudes and practices of doctors on end-of-life care by questionnaire survey in 2004 and 2008. Results: In 2004, 31.7% of the respondents agreed that they "do not attempt resuscitation" (DNAR) form was useful and it rose to 54.4% in 2008. A higher proportion of respondents in 2008 claimed that they signed the DNAR form for documentation and accepted withholding noninvasive life-sustaining treatment compared to 2004. In 2004, 50% of the respondents regarded their training and education on handling DNAR issue as inadequate. Conclusion: Documentation by DNAR form is gaining wider acceptance. Many doctors are expected to have more training and coaching on communication for handling such sensitive issues.